MEANING-FOCUSED INSTRUCTION (MFI) VS. FORM-FOCUSED INSTRUCTION (FFI): METAREFLECTION ON BIPA GRAMMAR LEARNING - Fida Pangesti Pangesti; Arti Prihatini; Joko Widodo (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
The purpose of this research is to explore the beliefs of BIPA (Indonesian Language for Foreign Speakers) instructors and learners regarding grammar instruction. This research is a descriptive-quantitative study. The subjects consist of 10 BIPA instructors and 20 BIPA learners from UPT BIPA Muhammadiyah Malang University, CIS BIPA State University of Malang, IAIN Surakarta Language Center, and UPT BIPA State University of Medan. The research data include quantitative and qualitative data related to the beliefs that BIPA instructors and learners regarding the instructional framework for grammar learning. Data were collected through a questionnaire adapted from Burgess and Etherington (2022) and interviews. The data were then analyzed using descriptive statistics and qualitative analysis, referring to the beliefs of BIPA instructors and learners regarding grammar instruction. The data analysis results showed that there are differences in beliefs between BIPA learners and instructors regarding the instructional model for teaching Indonesian grammar. BIPA learners believe that Form-Focused Instruction (FFI) is more effective in mastering Indonesian grammar because it focuses on rules and is taught explicitly and deductively, allowing learners to directly understand the target language rules. In contrast, instructors believe that Meaning-Focused Instruction (MFI) is the most suitable instructional model for teaching Indonesian grammar because it focuses on communicative aspects and taught implicitly and inductively, enabling learners to better apply the target language rules. To accommodate these differences in beliefs, an instructional model is needed to accommodate it with the following stages: (1) exposure, (2) formulation of grammar rules, (3) reinforcement of grammar rules, and (4) the use of grammar rules.